Flexible Ultrathin PolyDVB/EVB Composite Membranes for the Optimization of a Whole Blood Glucose Sensor. - Bridge, Kerry; Davis, Frank; Collyer, Stuart D.; Higson, Seamus P. J. (John Wiley & Sons, Ltd, 2007)
An ultrathin composite membrane has been developed as the outer covering barrier in a model amperometric glucose oxidase enzyme electrode. The membrane was formed by cathodic electropolymerization of divinylbenzene/ethylvinylbenzene at the surface of a gold coated polyester support membrane. Permeability coefficients were determined for O2 and glucose across membranes with a range of polymer thicknesses. Anionic interferents (such as ascorbate), were screened from the working electrode via a charge exclusion mechanism. The enzyme electrode showed an initial 10% signal drift when first exposed to whole human blood over a period of 2 hours, after which responses remained essentially stable. Whole blood patient glucose determinations yielded a correlation coefficient of r2=0.99 compared to standard hospital analyses.
Keywords: Cathodic electropolymerization; Composite membrane; Amperometric enzyme electrode; Polydivinylbenzene; Blood